2021
DOI: 10.3390/ijms22020639
|View full text |Cite
|
Sign up to set email alerts
|

Fission Yeast Methylenetetrahydrofolate Reductase Ensures Mitotic and Meiotic Chromosome Segregation Fidelity

Abstract: Methylenetetrahydrofolate reductase (MTHFR) is a key enzyme in the folate metabolic pathway, and its loss of function through polymorphisms is often associated with human conditions, including cancer, congenital heart disease, and Down syndrome. MTHFR is also required in the maintenance of heterochromatin, a crucial determinant of genomic stability and precise chromosomal segregation. Here, we characterize the function of a fission yeast gene met11+, which encodes a protein that is highly homologous to the mam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 56 publications
(30 reference statements)
0
4
0
Order By: Relevance
“…[7] In addition, dietary folates and related metabolic factors can also regulate MTHFR gene methylation and expression levels. [12,13] A recent study revealed that the fission yeast methylenetetrahydrofolate reductase protein (Met11) is important for maintaining the pericentromeric heterochromatin structure to ensure mitotic and meiotic chromosome segregation fidelity, [14] supporting the original hypothesis by James et al and suggesting that MTHFR polymorphisms promote changes in global DNA methylation during maternal meiosis leading to chromosomal non-disjunction and increasing the maternal risk to have children with DS. [6] In addition, both MTHFR C677T and A1298C polymorphisms have been linked to an increased risk of chromosome malsegregation in lymphocytes of mothers of DS children.…”
Section: Introductionmentioning
confidence: 64%
See 1 more Smart Citation
“…[7] In addition, dietary folates and related metabolic factors can also regulate MTHFR gene methylation and expression levels. [12,13] A recent study revealed that the fission yeast methylenetetrahydrofolate reductase protein (Met11) is important for maintaining the pericentromeric heterochromatin structure to ensure mitotic and meiotic chromosome segregation fidelity, [14] supporting the original hypothesis by James et al and suggesting that MTHFR polymorphisms promote changes in global DNA methylation during maternal meiosis leading to chromosomal non-disjunction and increasing the maternal risk to have children with DS. [6] In addition, both MTHFR C677T and A1298C polymorphisms have been linked to an increased risk of chromosome malsegregation in lymphocytes of mothers of DS children.…”
Section: Introductionmentioning
confidence: 64%
“…A recent study revealed that the fission yeast methylenetetrahydrofolate reductase protein (Met11) is important for maintaining the pericentromeric heterochromatin structure to ensure mitotic and meiotic chromosome segregation fidelity, [ 14 ] supporting the original hypothesis by James et al and suggesting that MTHFR polymorphisms promote changes in global DNA methylation during maternal meiosis leading to chromosomal non-disjunction and increasing the maternal risk to have children with DS. [ 6 ]…”
Section: Introductionmentioning
confidence: 78%
“…RNAi mutants host disruption of centromeric heterochromatin that compromises kinetochore function, resulting in hypersensitivity to microtubule depolymerizing drug thiabendazole (TBZ) [ 48 , 49 ]. To assess if the suppression of Δago1 and Δclr4 may similarly result in the TBZ hypersensitivity of these mutants, we performed serial dilution spotting assays on 8 and 15 µg/mL TBZ, to check TBZ sensitivity of the single and double mutants of 5-FU-resistant gene mutants combined with Δago1 and Δclr4 .…”
Section: Resultsmentioning
confidence: 99%
“…While most of these factors were missed by the previous genome-wide studies, other research reported several links to methionine and SAM synthesis. Methylenetetrahydrofolate reductase Met11 plays a role in methionine regeneration through 5-MTHF generation and was noted to affect heterochromatin integrity (Lim et al, 2021). Additionally, SAM synthetase was among the SU(VAR) mutants displaying altered position effect of variegation in flies (Larsson et al, 1996) and was further shown to be crucial for silencing and perinuclear heterochromatin anchoring in worms (Towbin et al, 2012).…”
Section: Discussionmentioning
confidence: 99%